Clinical and cost-effectiveness of parenting intervention for mothers experiencing psychosocial stress: insights from the early closure of the Mellow Babies RCT - Lucy Thompson; Jessica Tanner; Matthew Breckons; Naomi Young; Laura Ternent; Thenmalar Vadiveloo; Philip Wilson; Danny Wight; Louise Marryat; Iain McGowan; Graeme MacLennan; Angus MacBeth; et al. (Public Health Research)
Background Problems in children’s early social and emotional development are likely to have major long-term consequences for the individual and society: maternal emotional well-being is associated with better outcomes. Interventions designed to improve both maternal mental health and the mother–child relationship are thus likely to benefit both maternal health and child development. Objectives To establish the clinical and cost-effectiveness of the Mellow Babies parenting intervention for women experiencing psychosocial stress and their 6- to 18-month-old babies. Secondary aims included understanding the process of recruitment, retention and engagement in both the trial and the intervention. Design This was a single-centre randomised controlled trial, employing 1 : 1 randomisation with participants allocated to receive Mellow Babies plus usual care, or usual care only. Setting Community settings in the Highland Council region of Scotland. Participants We aimed to recruit 212 mothers to provide evaluable data for 170 participants (90% power to detect an effect size of 0.5 for the primary outcome). Eligible mothers lived within the Highland Council region; were aged ≥ 16 years; had primary caregiving responsibility of a baby aged 6–18 months and scored above threshold for anxiety (≥ 11) and/or depression (≥ 7) on the Hospital Anxiety and Depression Scale. Intervention Mellow Babies is a 14-week group-based parenting programme specifically designed for mothers with psychosocial difficulties. Sessions run for 5 hours each and include 4–10 participants. Main outcome measures Maternal Hospital Anxiety and Depression Scale scores at 8 months post randomisation and when the child reaches 30 months. Health economic (service use and quality of life) and child development (language development and mental well-being) outcomes were also examined. Results Due to the COVID-19 pandemic, the trial did not recruit to target: 106 women were recruited (53 per arm). It was not possible to explore the clinical and cost-effectiveness of Mellow Babies. Baseline, follow-up and process evaluation data were analysed to allow optimal learning from the study. Direct communication (letter) combined with health visitor referral was a better means of recruitment. Despite relatively low sociodemographic disadvantage, there was a high prevalence of mental ill health. Retention to follow-up and within the intervention was good (75% to study end point), and data were well-completed. Quality-of-life ratings increased at 8 months post randomisation, then decreased somewhat at 30 months of age, but remained above baseline. Qualitative interviews highlighted barriers and facilitators of engagement with the intervention groups. There was no observed difference in baseline characteristics or outcomes between participants recruited before and after the pandemic, although the logistical impact on the trial was profound. Limitations The study was not sufficiently powered to answer the main outcome questions. The occurrence of the COVID-19 pandemic severely hampered the current trial. Conclusions This trial was not able to answer questions on clinical and cost-effectiveness. Learning from this trial could inform a new re-designed trial including cluster randomisation and based within a larger and more varied population. Future work There is still a need for a definitive trial of Mellow Babies. It would likely be most fruitful to conduct a cluster randomised trial, with full buy-in from key health service stakeholders and front-line practitioners, to maximise recruitment, engagement and participation. Trial registration The trial is registered as ISRCTN47575326. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Public Health Research programme (NIHR award ref: 15/126/05) and is published in full in Public Health Research; Vol. 12, No. 17. See the NIHR Funding and Awards website for further award information. Plain language summary Why did we do this trial? There are links between mothers’ mental well-being, parenting behaviours and childhood mental health. Childhood social, emotional and development problems are connected to long-term health problems and other types of adversity, such as poverty and crime. We wanted to examine whether a group-based parenting intervention, ‘Mellow Babies’, would improve mothers’ mental well-being and children’s development and whether it represented value for money. What did we do? We aimed to recruit 212 women to take part. Women were eligible if they had a baby aged 6–18 months, lived in the Highland Council area (Scotland) and had moderate to high anxiety and/or depression symptoms. Half of the women were allocated randomly (like tossing a coin) to attend a 14-week Mellow Babies group alongside usual care, and the other half received usual care only (e.g. seeing their health visitor or attending a feeding clinic). Outcome data for mothers and babies were collected 8 months after recruitment and when babies were 30 months old. We interviewed mothers attending Mellow Babies groups and group facilitators. We had to pause recruitment for 20 months during the COVID-19 pandemic. What did we find? We were not able to recruit enough participants: 106 women took part. This means we could not compare the outcomes of mothers and babies who attended the Mellow Babies programme with those who did not or whether it was good value for money. Writing a letter to mothers was the most successful method of recruitment. Participants were generally more well-off than the local population (e.g. income, level of education) but they did experience significant mental ill health. A large proportion of participants stayed in the study until the final follow-up (75%). In interviews, participants highlighted barriers and facilitators of engagement with the intervention groups. Participants recruited before the pandemic were no different from those recruited afterwards. What did this mean? We cannot say definitively whether Mellow Babies is effective at improving mothers’ mental well-being or children’s developmental outcomes. A new larger trial is needed, building on The Mellow Babies Trial.